Transarterial Embolization for Hepatocellular Carcinoma: A Comparison between Nonspherical PVA and Microspheres - Scaffaro, Leandro Armani (Biomed Res Int, 2015)
Transarterial chemoembolization (TACE) and transarterial embolization (TAE) have improved the survival rates of patients with unresectable hepatocellular carcinoma (HCC); however, the optimal TACE/TAE embolic agent has not yet been identified. The aim of this study was to compare the effect of two different embolic agents such as microspheres (ME) and polyvinyl alcohol (PVA) on survival, tumor response, and complications in patients with HCC submitted to transarterial embolization (TAE). Eighty HCC patients who underwent TAE between June 2008 and December 2012 at a single center were retrospectively studied. A total of 48 and 32 patients were treated with PVA and ME, respectively. There were no significant differences in survival (P = 0.679) or tumoral response (P = 0.369) between groups (PVA or ME). Overall survival rates at 12, 18, 24, 36, and 48 months were 97.9, 88.8, 78.9, 53.4, and 21.4% in the PVA-TAE group and 100, 92.9, 76.6, 58.8, and 58% in the ME-TAE group (P = 0.734). Patients submitted to TAE with ME presented postembolization syndrome more frequently when compared with the PVA group (P = 0.02). According to our cohort, the choice of ME or PVA as embolizing agent had no significant impact on overall survival.